(untitled) (Praxis Educativa, 2022)
This article gives an account of the diagnosis to the process of pedagogical practices, from the study plans of pedagogy of the Faculty of Education and Humanities oriented to continuous improvement and which has allowed to compile the evidence that accounts for the diverse perceptions of the training, mentoring, collaborating, and graduated teachers from the University of Bio-Bio. This information is constituted from the training experience of the graduated cohorts in 2017, 2018 and 2019. The results were obtained from the participation and contributions of all the participating actors.